The choice of grammatical gender of the predicate matching the composite subject in contemporary Polish - Zbróg, Piotr (Papers in Linguistics, 2025)
Adapting the form of the predicate in terms of grammatical gender to the composite (compound) subject in ad sensum syntax is one of the fundamental problems of syntactic description in Polish sentences. There are several key determinants of whether the predicate will be in the masculine or non-masculine gender, cf. Kobieta i mężczyzna poszli do kina; Kobieta i pies bawili się / bawiły się na polu; Dziecko i kobieta uratowali się / uratowały się z pożaru. The article attempts to characterize at least three main types of syntactic alignment between the composite subject and its predicate in sentences excerpted from contemporary empirical material. Based on the analysis of contexts, it was established that with some composite subjects the predicate is usually masculine (e.g. when the subject includes a masculine personal noun), while in others it is non-masculine (e.g. when the subject consists of single-gender neuter nouns or feminine impersonal nouns). Different variants of the predicate form appear with composite subjects made of a feminine personal noun and any other noun. In each case, there were more or less numerous exceptions to the established rules.